Analysis of the Influence of Service Performance, Customer Relationship Marketing and Product Innovation on Customer Loyalty of Sharia Bank - Syahribulan Syahribulan; Syamsinar; Esti Nur Wakhidah; Prety Diawati; Sukriyadi (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2023)
This research aims to analyze customer relationship marketing's impact, service performance, and product innovation on customer loyalty. The sample for this study is Bank Muamalat Indonesia. The findings show simultaneously that customer relationship marketing, service performance, and product innovation together affect customer loyalty. The findings partially show that there is no significant influence of customer relationship marketing and service performance on customer loyalty. Although consumer loyalty is significantly influenced by product innovation.